Social Acceptance For Leprosy Infants: Case Study of Leprosy Village, in Balang Baru Village in Makassar City (CV. Literasi Indonesia, 2023)
The study delves into societal perceptions and interactions with leprosy-affected individuals in Balang Baru's Leprosy Village, addressing the prevalent negative stigma that shapes their social relationships. While striving for a more inclusive social space, affected individuals often experience alienation, limiting their interactions. Utilizing qualitative methods, including observation, interviews, and documentation, the research focuses on individuals impacted by leprosy, former patients, and the local community. Findings reveal a contrasting dynamic: within Balang Baru, residents view affected individuals as ordinary, fostering acceptance due to shared experiences. However, external societal acceptance remains scarce, hindering their engagement beyond the community. This study underscores the disparities in perception and interaction between internal and external environments. The challenge ahead lies in integrating affected individuals into broader society, necessitating bridging the gap between localized acceptance and the broader societal stigma. Ultimately, the research emphasizes the need to facilitate the inclusion of leprosy-affected individuals in the wider society beyond their immediate community.